2023
DOI: 10.3390/plants12030574
|View full text |Cite
|
Sign up to set email alerts
|

Disadvantaged Economic Conditions and Stricter Border Rules Shape Afghan Refugees’ Ethnobotany: Insights from Kohat District, NW Pakistan

Abstract: The study of migrants’ ethnobotany can help to address the diverse socio-ecological factors affecting temporal and spatial changes in local ecological knowledge (LEK). Through semi-structured and in-depth conversations with ninety interviewees among local Pathans and Afghan refugees in Kohat District, NW Pakistan, one hundred and forty-five wild plant and mushroom folk taxa were recorded. The plants quoted by Afghan refugees living inside and outside the camps tend to converge, while the Afghan data showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In the current global situation, the fact that some villages have reported little to no use of certain plants is a concerning indication of knowledge erosion over time [ 37 , 38 ]. This underscores the urgent need for continued ethnobotanical research to document and preserve traditional knowledge, as well as to identify and address the factors contributing to the loss of this invaluable cultural heritage.…”
Section: Discussionmentioning
confidence: 99%
“…In the current global situation, the fact that some villages have reported little to no use of certain plants is a concerning indication of knowledge erosion over time [ 37 , 38 ]. This underscores the urgent need for continued ethnobotanical research to document and preserve traditional knowledge, as well as to identify and address the factors contributing to the loss of this invaluable cultural heritage.…”
Section: Discussionmentioning
confidence: 99%
“…The representation of some migration could have inflated by this latter percentage flows when one study reported more than one migration flow, such as those from the African continent to the American continent [26-27; yet it only partially reflects the massive and violent migration due to slavery). About 15% of migration flows were of refugees, including war refugees [28,31] and refugees after the beginning of an authoritarian government [32]. For another 15% of the studied migrations, the movement occurred more than 150 years ago.…”
Section: How Migrations and Food Plants Are Being Studiedmentioning
confidence: 99%
“…Christenh. and Byng among Afghan refugees in Pakistan [31]; and, among multiethnic migrants in Guatemala, the fruits of Chamaedorea tepejilote Liebm. in Mart., Pouteria sapota (Jacq.)…”
Section: Migration Effects On Plant Management Knowledge and Usementioning
confidence: 99%
See 2 more Smart Citations